Poetry: a powerful reading intervention for accuracy and fluency - Thompson, Kimberly Penny (My University, 2013)
Due to the increasing pressure to meet Common Core State Standards for more essential curriculum components, poetry is often an overlooked foundation of the literacy curriculum. Students today demonstrate a lack of knowledge in the genre poetry. In spite of this, poetry is an important Common Core English Language Arts standard which asks K-12 students to be fluent in and identify parts of stories, dramas, and poems when writing or speaking about a text, using terms such as chapter, scene, and stanza. This qualitative study aims to identify ways to implement poetry in the classroom on a consistent basis to promote student confidence, reading fluency, word recognition, engagement, connection, and comprehension. Third grade students were pre assessed and post assessed using reading attitude surveys, 3rd grade Dolch sight words, and DRA2 reading assessments to measure fluency and accuracy. My prediction for the study was students' reading confidence would increase allowing for growth in reading attitudes and reading fluency and accuracy.
Plan B Paper. 2013. Master of Science in Education- Reading--University of Wisconsin-River Falls. Teacher Education Department. 68 leaves. Includes bibliographical references (leaves 26-27).
Keywords: Reading (Elementary); Poetry--Study and teaching (Elementary)